Hoffman’s syndrome-a rare neurological presentation of hypothyroid myopathy - Sriharsha, Tirumalasetty; Kumar, A. Arun; Raj J., Raghav; Reddy, N. Monika; V., Vikrannth; Raghavan, Vinod; Rajendran, Kannan (International Journal of Advances in Medicine, 2022)
Hoffman's syndrome is a rare form of hypothyroid myopathy, which causes proximal muscle weakness and pseudohypertrophy of muscles. It is a complication of untreated or uncontrolled Hypothyroidism.The neurological manifestations of hypothyroidism usually occur late in the course of disease. It is quite rare to present with neurological manifestations in the earlier stage of disease. Very few cases of Hoffman’s syndrome were reported from India. Here we report a case of 27-year-old male who presented to the medicine OPD with initial symptoms of proximal muscle weakness, fatigue and calf muscle hypertrophy. On further evaluation patient was found to have hypothyroid myopathy in the form of Hoffman’s syndrome.